2013
DOI: 10.1002/hep.26109
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mammalian target of rapamycin aggravates the respiratory burst defect of neutrophils from decompensated patients with cirrhosis

Abstract: Cirrhosis is commonly accompanied by impaired defense functions of polymorphonuclear leucocytes (PMNs), increased patient susceptibility to infections, and hepatocellular carcinoma (HCC). PMN antimicrobial activity is dependent on a massive production of reactive oxygen species (ROS) by nicotinamide adenine dinucleotide phosphate (NADPH) 2 (NADPH oxidase 2; NOX2), termed respiratory burst (RB). Rapamycin, an antagonist of mammalian target of rapamycin (mTOR), may be used in the treatment of HCC and in transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…It is known that this microbicidal mechanism is reactive oxygen species (ROS) dependent [13]; it has been demonstrated that neutrophils in patients with liver diseases present defects in the production of ROS, mainly in the production of superoxide anion and hydrogen peroxide [14]. This could be the cause of the deficient capability of NETs release in patients with LC, and it could also be involved in the high incidence of bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that this microbicidal mechanism is reactive oxygen species (ROS) dependent [13]; it has been demonstrated that neutrophils in patients with liver diseases present defects in the production of ROS, mainly in the production of superoxide anion and hydrogen peroxide [14]. This could be the cause of the deficient capability of NETs release in patients with LC, and it could also be involved in the high incidence of bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Due to space constraints, this section is detailed in the Supplementary Material, and includes neutrophil isolation [8], MPO exocytosis and assay [37], bactericidal activity [8], western-blot analyses of protein phosphorylation [8] and RNA quantification.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the MPO intracellular pool was not impaired, which suggests that the deficient MPO release induced by fMLP in patients' neutrophils ( Fig 1A and B) may likely due to altered fPR-mediated signaling. To further explore this hypothesis, neutrophils were stimulated under optimal conditions with fMLP and the activated phosphorylated form of major signaling effectors was western-blotted [8,38,39]. Stimulation of healthy neutrophils induced a rapid phosphorylation of AKT, p38-MAPK and p44/42-MAPK (ERK1/2) ( Fig.…”
Section: Severe Impairment Of Fmlp-induced Mpo Release and Signaling mentioning
confidence: 99%
See 2 more Smart Citations